MAIN DEVELOPMENTS IN INDIAN BANKING AND THE CHOICE PROCESS OF CONSUMERS IN BANK SELECTION - POPLI, ANSHUL (2012)
ABSTRACT This research was carried on to high lighten the main developments of banking in India and the choice process of consumers in the selection of bank. It mainly focuses on what all factors do consumers take into account in their selection process. This shows how important it is for retail banks to understand the choice making of the potential consumers and thereby develop appropriate marketing strategies to attract them. The sample of the study involves 20 consumers. There are a total of 10 factors on which consumers were interviewed identified from the researcher’s personal experience, literature review, observations and interviews. The result was that the main factors that drive the consumer selection process are location, service quality, friendliness and connectivity. It also shows that male consumers and female consumers have different criteria in the selection process. Also to improve their relationships with the customer the banks need to be flexible enough to cope up with the changes and build up good channels of communication with their customers and thereby develop appropriate marketing strategies.